Paleoproterozoic to Cenozoic zircon U–Pb ages with Hf signatures from metamorphic rocks and granodiorite of Tokunoshima: constraints on the geotectonic subdivision of the Ryukyu island arc, Southwest Japan. Issue 3 (4th February 2022) - Yamamoto, Hiroshi; Okamoto, Kazuaki; Chung, Sun-Lin; Lee, Hao-Yang; Mita, Yuji; Ueda, Shuro; Terabayashi, Masaru
ABSTRACT: LA-ICP-MS U–Pb and Hf isotope analysis was conducted on zircons from the metamorphic unit of Omo Formation and a granodorite body of Tokunoshima in the Amami Islands, Southwest Japan. Zircons from dioritic gneiss (S9, S46) and pelitic schist (S99) yielded Paleoproterozoic upper intercept and Early Jurassic lower intercept ages. The positive εHf (t) values of the Paleoproterozoic zircons (between +12.7 and 0.8) and the negative εHf (t) values of the Jurassic zircons (−19.6 and −22.8) indicate Early Jurassic reworking of the older continental crust. The results suggest that the Omo Formation is an eastern equivalent of Cathaysia of the South China block. Zircons from granodiorite (S62) yielded a 206 Pb/ 238 U mean age of 61.3 ± 1.0 Ma with positive εHf (t) values of +12.0 and +12.6. The εHf (t) values indicate juvenile magmatic activity, which is correlated with that in the San-in batholith belt of Southwest Japan. Dioritic gneiss (S30) and psammitic schist (P91) yielded zircon U–Pb ages comparable to that of granodiorite (S62) with positive εHf (t) values (from +6.4 to +10.4). This suggests that the intrusion of the granodiorite induced the crystallization of zircon grains in the host rocks.